Applications of Base Editing Technology in Modifications of Pig Genes - Jiasheng PAN; Qiuyan HUANG; Yecheng YANG; Shuaipeng YANG; Xiangxing ZHU; Dongsheng TANG (Guangdong nongye kexue, 2022)
Pigs are highly valued in both agriculture and medicine. We can quickly improve the economic properties of pigs and develop human disease models via gene modification technologies. CRISPR/Cas9 gene editing technology, with the advantages of simple operation, high efficiency and low cost, is widely applied in modifying pig genes. However, CRISPR/Cas9, due to its proneness to cause problems including structural instability of the genomes, large-scale chromosomal rearrangement and gene off-target, could pose potential risks to biological safety. In recent years, the base editing technology based on CRISPR/Cas9 can achieve the directional conversion of a single base without causing DNA double-strand breaks and insertion or loss (Indels), which is more precise and safer for gene editing. With the continuous development and improvement of base editing tools, it is not only able to produce base C → T (A → G) mutations, but also to produce simultaneous mutations of two bases (C and A) and base C → G, increasing the scope of application. improved base editing tools can reduce or even eliminate collateral mutations while maintaining editing efficiency, no C → T (A → G) mutations and Indels, making base editing technology has more important potential applications in pig genetic modification. In order to provide references for the application of base editing in pigs, the study reviews the systemic mechanism of different base editing technologies, the application of base editing technologies in the construction of genetically modified pig models and the genetic improvement of pigs as well as the editing efficiency and off-target situation of base editing systems in pig fibroblasts.